Organic, organomineral, and mineral fertilizers with urease and nitrification inhibitors for wheat and corn under no-tillage - Correa, Juliano Corulli; Grohskopf, Marco Andre [UNESP]; Nicoloso, Rodrigo da Silveira; Lourenco, Kesia Silva; Martini, Rosemari (Empresa Brasil Pesq Agropec, 2016)
The objective of this work was to evaluate soil chemical attributes, leaf nitrogen content, and corn and wheat yields under a no-tillage system in response to the application of organic, organomineral, and mineral fertilizers with or without urease and nitrification inhibitors. The experiment was carried out on the field, with one wheat and two corn crops, on a Rhodic Kandiudox, in a randomized complete block design with six replicates. The evaluated treatments were: control, without fertilization; O, poultry litter as an organic fertilizer; O+I, poultry litter and inhibitors; OM, organomineral fertilizer; OM+I, organomineral fertilizer and inhibitors; U, urea as a mineral fertilizer; and U+I, super urea with the urease inhibitor alone. The use of organic, organomineral, and mineral fertilizers, with or without inhibitors, increased available N content in the 0.00-0.05-m soil layer. In deeper layers, only OM+I in the 0.05-0.10-m layer and U+I in the 0.10-0.20-m layer provided higher contents than the control treatment. Leaf N contents were adequate, regardless of the fertilizer used. The O, O+I, OM, and OM+I treatments increase available P content and base saturation, and decrease H+Al on soil surface. Moreover, all fertilizers increase total grain yield of the two studied crops, in the following order: OM+I > U+I >= U > OM >= O+I = O.
Keywords: Triticum aestivum; Zea mays; agronomic efficiency; poultry litter; nitrogen fertilization; volatilization losses